(untitled) (The Lumbini Journal of Business and Economics, 2026)
Purpose: The goal of the study is to determine how well-informed Kathmandu Valley consumers are about biometric authentication as a payment option. Additionally, the study evaluates the variables influencing consumers’ propensity to use biometric authentication as a payment method. Methods: This study employs an explanatory research design. Purposive sampling was used to select a sample of 403 respondents. It makes use of the Unified Theory of Acceptance and Use of Technology (UTAUT). Two descriptive and inferential statistics were employed to analyze the data. The data was analyzed using SEM. Results: The findings indicate that attitude has a substantial impact on intention to use (β = 0.472, p & Iu; 0.000), perceived usefulness (β = -0.260, p & Iu; 0.000), and perceived ease of use (β = 0.279, p & Iu; 0.000). Additionally, intention to utilize is significantly negatively impacted by trust (β = -0.221, p = 0.000). Social influence has a negligible impact on the intention to use biometric authentication (β = 0.028, p = 0.535). Conclusion: According to this study, Usage Intention is directly impacted by Perceived Ease of Use, Perceived Usefulness, Attitude, Social Influence, and Trust, with Perceived Ease of Use, Perceived Usefulness, Attitude, and Trust having a major impact.